2022
DOI: 10.1111/bjso.12521
|View full text |Cite
|
Sign up to set email alerts
|

Can culture beat Covid‐19? Evidence that exposure to facemasks with cultural symbols increases solidarity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Another potential limitation regarding color is that its effect is context dependent, as emphasized by color-in-context theory 28 , 29 . Some studies exploring mask perception have shown that, contrary to their classically negative perception, masks can communicate positive representations like trustworthiness and security during a pandemic 82 , 83 . The manipulation of a positive versus negative interactional context might therefore modulate the meaning of the mask, and thus shed further light on the effect of colored masks in face processing.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation regarding color is that its effect is context dependent, as emphasized by color-in-context theory 28 , 29 . Some studies exploring mask perception have shown that, contrary to their classically negative perception, masks can communicate positive representations like trustworthiness and security during a pandemic 82 , 83 . The manipulation of a positive versus negative interactional context might therefore modulate the meaning of the mask, and thus shed further light on the effect of colored masks in face processing.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous research on symbols and identity. For example, Perach and Limbu (2022) report that masks with cultural symbols can increase positive interpersonal perceptions of people whose symbols represent meaningful social identities during the COVID-19 pandemic. Moreover, it is not only the contemporary cultural symbols that can elicit identification but also identification with traditional cultural symbols in our society ( Monge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result also applies to face masks. For example, Perach and Limbu (2022) used cultural masks (face masks with cultural symbols representing unity) as experimental materials and found that cultural masks significantly increased facial trust ratings. This finding offers helpful suggestions for interpersonal communication during and after pandemics.…”
Section: Mask and Social Judgmentmentioning
confidence: 99%